Subsidizing firm entry in open economies - Michael Pflüger; Jens Südekum (Institute for the Study of Labor (IZA), 2009)
Entrepreneurs who decide to enter an industry are faced with different levels of effective entry costs in different countries. These costs are heavily influenced by economic policy. What is not well understood is how international trade affects the government incentive to impact on entry costs, and how entry subsidies can be used strategically in open economies. We present a general equilibrium model of monopolistic competition with two (potentially) asymmetric countries and heterogeneous firms where government subsidizes entry of domestic entrepreneurs. Under autarky the entry subsidy indirectly corrects for the monopoly pricing distortion. In the autarky equilibrium these subsidies trigger entry, but they eventually do not lead to more but to better firms in the market. In the open economy there is another, strategic motive for entry subsidies as the tightening of domestic market selection also affects exporting decisions for domestic and foreign firms. Our analysis shows that entry subsidies in the Nash-equilibrium are first increasing, then decreasing in the level of trade openness. This implies a U-shaped relationship between openness and effective entry costs. Merging cross-country data on entry costs with international trade openness indices we empirically confirm this theoretical prediction.
urn:nbn:de:101:1-200910086460
Keywords: F12; F13; H25; L11; 330; Firm entry; subsidies; heterogeneous firms; international trade; monopolistic competition; entry regulation; strategic trade policy; Markteintritt; Unternehmer; Subvention; Monopolistischer Wettbewerb; Außenwirtschaft; Offene Volkswirtschaft; Strategische Handelspolitik; Theorie